PERAN GURU AKIDAH AKHLAK DALAM PEMBINAAN AKHLAK PESERTA DIDIK DI SDIT AL-MUZZAMMIL BEKASI KECAMATAN JATIASIH KOTA BEKASI - Muhamad Nur Taufik (UNISAN JURNAL, 2025)
This study aims to analyze and describe the role of Akidah Akhlak teachers in fostering students’ morals. This study uses a qualitative approach because the data collected is descriptive and not in the form of numbers. Data collection techniques used include observation, interviews, and documentation studies. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. Based on the results of the study, it is known that the role of Akidah Akhlak teachers as educators has not been running optimally. This is due to several factors, such as the limited frequency of meetings between teachers and students, the lack of monitoring of student development through portfolio assessments, and the lack of intensive instillation of moral values. In addition, teachers are also considered to have less mastery of learning materials, do not prepare learning programs well, and have not carried out the learning process and its evaluation optimally. However, Akidah Akhlak teachers have shown good role models in terms of speech, attitude, and appearance, especially in dressing in accordance with Islamic values. However, role models in aspects of worship and responsibility for tasks still need to be improved. Therefore, in order for the role of Akidah Akhlak teachers in fostering the morals of students at SDIT Al-Muzzammil Bekasi to be more optimal, teachers need to increase their activeness, creativity, and innovation in carrying out their functions as educators, teachers, and role models for students